2000
DOI: 10.1038/modpathol.3880237
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Multinucleated Giant Cells in Lymphoid Tissue of the Waldeyer's Ring: A Detailed Study

Abstract: Hyperplastic lymphoid tissues of the Waldeyer's ring in human immunodeficiency virus (HIV)-infected patients may occasionally contain multinucleated giant cells (MGCs). These cells, which are unrelated to any opportunistic infection, previously have been demonstrated to harbor significant amounts of HIV. Studies undertaken to characterize these MGCs have generated conflicting results: some reports suggested a macrophage origin, whereas others supported a dendritic cell lineage. This study was performed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…When human macrophages infected with Dnef-HIV-1 or wt viruses were compared, we observed that formation of MGCs (or syncytia) was diminished in Dnef-HIV-1-infected cells, whereas Dnef-HIV-1 and wt-HIV-1 infectivities of human macrophages were similar. In AIDS patients, MGCs have been shown to be of macrophage origin (7)(8)(9), but the mechanisms involved in their formation in vivo or in vitro have not been studied. Also HIV-1-infected CD4 + lymphocytes form giant cells in vitro, but until now, they have not been observed in AIDS patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When human macrophages infected with Dnef-HIV-1 or wt viruses were compared, we observed that formation of MGCs (or syncytia) was diminished in Dnef-HIV-1-infected cells, whereas Dnef-HIV-1 and wt-HIV-1 infectivities of human macrophages were similar. In AIDS patients, MGCs have been shown to be of macrophage origin (7)(8)(9), but the mechanisms involved in their formation in vivo or in vitro have not been studied. Also HIV-1-infected CD4 + lymphocytes form giant cells in vitro, but until now, they have not been observed in AIDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathologies involve the formation of giant macrophages, but it is not clear whether it is beneficial or detrimental for patients (12). Giant macrophages have been described in the brains of AIDS patients as a marker for disease progression associated with HIV-induced dementia (7) and in lymphoid tissues of Waldeyer's ring in 66.7% of HIV-infected patients (8). HIV-infected T cells also form giant cells, but they rapidly undergo apoptosis (10), probably explaining why giant HIV-1-infected lymphocytes have not been observed in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HIV involvement of the intraparotid and pharyngeal lymphoid tissue may lead to marked hypertrophy of these structures [5][6][7], whereas in the orofacial region, widespread lesions of viral and fungal infections, as well as dental caries, may occur [1,3,8]. HIV-infected children may also suffer from hearing loss of either peripheral or central origin [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Multinucleated giant cells were present in 67% of biopsy samples of HIV patients with lymphoid hyperplasia. Their presence should suggest the possibility of an underlying HIV infection [5] . Treatment options in symptomatic patients with adenotonsillar hypertrophy have previously been limited to surgical resection.…”
Section: Discussionmentioning
confidence: 99%